2000
DOI: 10.1128/aac.44.6.1630-1638.2000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Sterol Biosynthesis and Amphotericin B Reduce the Viability of Pneumocystis carinii f. sp. carinii

Abstract: Pneumocystis carinii synthesizes sterols with a double bond at C-7 of the sterol nucleus and an alkyl group with one or two carbons at C-24 of the side chain. Also, some human-derived Pneumocystis carinii f. sp. hominis strains contain lanosterol derivatives with an alkyl group at C-24. These unique sterols have not been found in other pathogens of mammalian lungs. Thus, P. carinii may have important differences in its susceptibility to drugs known to block reactions in ergosterol biosynthesis in other fungi. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…With the exception of some plant pathogenic rust fungi in the class Uredinales, production and accumulation of C 28 and C 29 ⌬ 7 24-alkylsterols are not typical of most fungi (33). The efficacy of the sterol ⌬ 8 -tosterol ⌬ 7 inhibitor AY 9944 in reducing P. carinii viability (21) indicates that this modification of the sterol nucleus may be another excellent target for the development of chemotherapeutic agents against this ubiquitous opportunistic pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of some plant pathogenic rust fungi in the class Uredinales, production and accumulation of C 28 and C 29 ⌬ 7 24-alkylsterols are not typical of most fungi (33). The efficacy of the sterol ⌬ 8 -tosterol ⌬ 7 inhibitor AY 9944 in reducing P. carinii viability (21) indicates that this modification of the sterol nucleus may be another excellent target for the development of chemotherapeutic agents against this ubiquitous opportunistic pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…20-Piperidin-2-yl-5 ␣ -pregnan-3 ␤ -20( R )-diol and 24,25-( R , S )-epiminolanosterol were reported to inhibit both the proliferation of P. carinii in vitro (static activity) and the accumulation of 24-alkylsterols, presumably as a consequence of SAM:SMT inhibition (17). In another study, it was shown that 24,25-epiminolanosterol did not kill P. carinii organisms; however, several other inhibitors that target different reactions in sterol biosynthesis had cidal activity against P. carinii in vitro (21).…”
mentioning
confidence: 99%
“…Biofilm formation was measured by a ATP bioluminescence assay used extensively by our lab to assess the viability of Pneumocystis (5,(7)(8)(9)27). The assay is similar in concept to the XTT reduction assay used for fungal biofilm growth, which assesses mitochondrial function, but is a more sensitive and rapid method.…”
Section: Methodsmentioning
confidence: 99%
“…Drugs affecting genes in the essential eukaryotic core are likely to be broad spectrum in the fungal kingdom, for which there are few effective therapies (Georgopapadakou and Walsh 1994;Kaneshiro et al 2000). All known drug targets for Pneumocystis are associated with sterol metabolism, and resistance is already reported (Beard et al 2000) for the two major drugs for Pneumocystis pneumonia.…”
Section: Resultsmentioning
confidence: 99%